Educated Unemployed, Educational Subsidies and Growth (The Pakistan Development Review, 1984)
The subject matter of the present study is educated unemployment, a commonly observed phenomenon. especially in some of the more populous LDCs like India. Such an inquiry is warranted for two different reasons. First of all, It is a common observation that educated unemployment does not deter the demand for education; see, for example, Blaug et at. [3]. The question that needs to be answered is why do people go in for education in spite of this widespread unemployment? Secondly, it is an important policy question for governments of such LDCs as to whether education should be subsidized or not. Whereas the long-term gains in productivity accruing from a more educated labour force are undeniable, there is now also a growing realization that educational subsidies, by affecting educational costs, have a part to play in increased educated unemployment. In addition, such subsidies, being financed by taxes, reduce disposable income and hence further reduce an already inadequate supply of domestic savings for physical capital formation.